KONSTRUKSI SOSIAL SISWA SMA TERHADAP MITOS BUYUT CILI SEBAGAI TRADISI LISAN SEJARAH BLAMBANGAN - Suprijono, Agus (Paramita: Historical Studies Journal, 2013)
The research focused on a social construction or interpretation of the Buyut Cili Myth as a storytelling tradition Blambangan history. The research objectives identified socially constructed form of knowledge as well as the values of the Buyut Cili myth. The research method was classroom action research. The result of the research found that Buyut Cili myth was a conceptual instrument for students to understand the concept of historical continuity. The complexity of life was contained in reality which displayed by the Buyut Cili. It proved that social reality was plural or multi-dimension. The Myth of Buyut Cili is as a learning resource to achieve basic competence to describe the historical tradition in Indonesian society during the prehistory and historyÃ¢â‚¬Â consisted of historical, religious, cultural, social, and economic values, that needed for studentsÃ¢â‚¬â„¢ character education.Keywords: social construction, buyut cili myth, oral traditionÃ‚Â Fokus penelitian adalah konstruksi sosial atau pemaknaan terhadap mitos Buyut Cili sebagai tradisi lisan sejarah Blambangan. Tujuan penelitian mengidentifikasi hasil konstruksi sosial berupa pengetahuan maupun nilai-nilai dari mitos Buyut Cili. Metode penelitian adalah classroom action research. Hasil penelitian adalah mitos Buyut CiliÃ‚Â  merupakan instrumen konseptual bagi siswa memahami konsep kesinambungan sejarah. Kompleksitas kehidupan terkandung pada realitas yang ditampilkan oleh mitos Buyut Cili membuktikan bahwa realitas sosial atau kenyataan sosial bersifat jamak atau multidimensional. Mitos Buyut Cili sebagai sumber belajar untuk mencapai kompetensi dasar Ã¢â‚¬Å“mendeskripsikan tradisi sejarah dalam masyarakat Indonesia masa pra-aksara dan masa aksaraÃ¢â‚¬Â sarat nilai historis, agama, budaya, sosial, dan ekonomi yang urgen untuk pendidikan karakter siswa. Kata kunci: konstruksi sosial, mitos buyut cili, tradisi lisan Ã‚Â Ã‚Â